New Discourses on Energy Transition as an Opportunity for Reconciliation? Analyzing Indigenous and Non-Indigenous Communications in Media and Policy Documents - Mang-Benza, Carelle; Baxter, Jamie; Smith Fullerton, Romayne (The International Indigenous Policy Journal, 2021)
This article examines energy issues articulated by Indigenous and non-Indigenous people in Canada and analyzes the energy transition as a locus of reconciliation therein. Using content and discourse analysis of policy documents, white papers, and news media articles, we draw attention to reconciliation and energy discourses before and after 2015, the year that marked the release of the Truth and Reconciliation Commission of Canada (TRC) report and the Paris Agreement on climate change. We find a three-fold expansion of those discourses, which encompass issues of inclusion and exclusion, dependency, and autonomy, as well as colonial representations of Indigenous people, after 2015. We also find that non-Indigenous voices are more prominent in those conversations. We suggest that the prospects of mutual benefits could turn the energy transition into an opportunity to bring together Indigenous and non-Indigenous people in Canada.